Pengaruh Cita Rasa dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT.XYZ Depok - Alya Tri Suci Wulandari; Musthafa Kamil (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
XYZ (Company name disguised at the request of the company) is a well-established bakery industry in Indonesia. In running its business, of course, the company not only provides quality products and taste, but also provides good service quality because it can increase customer satisfaction. The purpose of this study is to determine the influence of taste and service quality on customer satisfaction of PT. XYZ Depok. The research method used is quantitative statistics. The population of this study is consumers who buy PT. XYZ Depok. Data collection methods with interviews, documentation, and questionnaires. Data processing using SPSS 25 with multiple linear regression analysis technique. Based on the results of the study, it was shown that taste had a significant effect on customer satisfaction and service quality also had a significant effect on customer satisfaction at PT. XYZ Depok, then the taste and quality of customers simultaneously have a significant effect on customer satisfaction at PT. XYZ Depok.